Cyclization of gold acetylides: synthesis of vinyl sulfonates via gold vinylidene complexes - Bucher, Janina; Wurm, Thomas; Nalivela, Kumara Swamy; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2014)
Differently substituted terminal alkynes that bear sulfonate leaving groups at an appropriate distance were converted in the presence of a propynyl gold(I) precatalyst. After initial formation of a gold acetylide, a cyclization takes place at the β-carbon atom of this species. Mechanistic studies support a mechanism that is related to that of dual gold-catalyzed reactions, but for the new substrates, only one gold atom is needed for substrate activation. After formation of a gold vinylidene complex, which forms a tight contact ion pair with the sulfonate leaving group, recombination of the two parts delivers vinyl sulfonates, which are valuable targets that can serve as precursors for cross-coupling reactions, for example.